Narrow-band UVB phototherapy in patients with atopic dermatitis: analysis of the factors determining treatment efficacy - Vadim V. Chikin; Arfenya E. Karamova; Alexey A. Kubanov; Maryanna B. Zhilova; Pavel V. Gorodnichev; Kseniya M. Aulova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Background. Efficacy the narrow-band UVB phototherapy in patients with atopic dermatitis varies greatly. An important condition for achieving optimal therapeutic effect is the identification of factors that can impact on the efficacy of therapy and considering their influence when prescribing treatment. Aims. The present study aimed to identify the factors which affect the efficacy of narrow-band phototherapy in patients with atopic dermatitis Methods. A prospective, open-label trial was conducted to evaluate the efficacy and safety of narrow-band UVB phototherapy for patients with moderate-to-severe atopic dermatitis. All patients were treated with narrow-band UVB phototherapy four times weekly for 5 weeks. Disease severity was evaluated by SCORing of the Atopic Dermatitis Index (SCORAD) and Eczema Area and Severity Index (EASI). Distribution of patients by the severity of therapeutic effect was evaluated. To compare the efficacy of therapy depending on initial atopic dermatitis severity, initial and cumulative irradiation doses, skin phototype, and smoking status patients were divided into subgroups. Results. 40 patients with moderate-to-severe atopic dermatitis received course of narrow-band UVB phototherapy. After NB-UVB therapy SCORAD and EASI scores reduced from 45.6 ± 11.4 at baseline to 22.6 ± 12.4 (p 0,05) and from 14.4 ± 7.2 at baseline to 4.1 ± 3.9 (p 0,05) respectively demonstrating the efficacy of narrow-band UVB phototherapy in patients with atopic dermatitis. Our investigation showed that tobacco smokers had definitely lower efficacy of NB-UVB phototherapy in comparison with non-smokers. Narrow-band UVB phototherapy had definitely higher efficacy when it is started with an initial dose 0.2-0.3 J/cm2 chosen in compliance with results of MED determing in comparison with an initial dose 0.05-0.15 J/cm2 selected according to skin phototype. Conclusions. Factors that impact on the efficacy of narrow-band UVB phototherapy in patients with atopic dermatitis were identified. It was determined that using higher initial dose is associated with higher efficacy of therapy. The obtained data suggest the opportunity of decrease in efficacy of therapy in smokers with atopic dermatitis.